Control development and performance evaluation for battery/flywheel hybrid energy storage solutions to mitigate load fluctuations in all-electric ship propulsion systems. (15th February 2018) - Hou, Jun; Sun, Jing; Hofmann, Heath
Highlights: A new B/FW HESS is proposed to isolate load fluctuations from the shipboard network. A periodic DP algorithm is developed to reduce the computational cost. A comparative study illustrates the advantages and limitations of B/UC and B/FW HESS. A novel MPC-based approach is developed to facilitate real-time implementation. The proposed MPC is validated in a laboratory-scaled experiment. Abstract: Current trends in both commercial and military ship development have focused on ship electrification. A challenge for electric-ship propulsion systems, however, is large propulsion-load fluctuations. To address this issue, this paper explores a new solution, namely a combined battery and flywheel (B/FW) hybrid energy storage system (HESS) as a buffer to isolate load fluctuations from the shipboard network. Our two main objectives, power-fluctuation compensation and energy saving under various operating constraints, are formulated as a multi-objective optimization problem. Pareto fronts, which illustrate the trade-offs between the main objectives, are obtained by using dynamic programming with the weighted sum method. To quantitatively analyze the performance of B/FW HESS, a comparative study is performed under different sea conditions, where a battery/ultra-capacitor (B/UC) HESS configuration is used as a reference in performance evaluation. Simulation results show the feasibility and effectiveness of B/FW to mitigate the load fluctuations for all-electric ships, especially at high sea states. Furthermore, a model predictive control (MPC) algorithm is developed to facilitate real-time implementation of the proposed solution. A performance comparison between the proposed MPC energy management strategy and the global dynamic programming is performed, and this comparison demonstrates the effectiveness of the proposed MPC strategy.